Panic Disorder 2016
DOI: 10.1007/978-3-319-12538-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Opioidergic Vulnerability Through Early Life Separation: A Recent Extension of the False Suffocation Alarm Theory of Panic Disorder

Abstract: We briefly reference previous material on Klein's suffocation false alarm theory (SFA) of panic disorder (Klein, 1993) and its amplification in 2008 (Preter andKlein, 2008). We then discuss a recent finding showing a fundamental difference in opioidergic reactivity to a naloxone challenge in psychiatrically and medically healthy adults, based on the presence or absence of childhood separation/parental loss.In 1993, Klein published the original SFA theory of panic disorder (Klein, 1993), attempting to integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 109 publications
0
4
0
1
Order By: Relevance
“…Under stressful conditions, the opioid system undergoes considerable changes that contribute to the regulation of several behaviors such as nociception, addiction, and seizure susceptibility [9][10][11]. In this regard, recent studies reported that experiencing adversity during childhood such as MS induced long-lasting alterations in the regulation of the endogenous opioid system in both humans and animals [12,13]. In this respect, previous research reported that MS stress reduced the pain threshold in animals and that this effect was correlated with hypofunction of the opioid system in the CNS [14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…Under stressful conditions, the opioid system undergoes considerable changes that contribute to the regulation of several behaviors such as nociception, addiction, and seizure susceptibility [9][10][11]. In this regard, recent studies reported that experiencing adversity during childhood such as MS induced long-lasting alterations in the regulation of the endogenous opioid system in both humans and animals [12,13]. In this respect, previous research reported that MS stress reduced the pain threshold in animals and that this effect was correlated with hypofunction of the opioid system in the CNS [14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…Ad oggi non vi sono evidenze sufficienti per l'identificazione di un locus genetico altamente correlato alla sintomatologia del DP ed i substrati anatomofunzionali responsabili della patogenesi del disturbo rimangono ancora poco conosciuti (Perna et al, 2014;Santos et al, 2015). L'ipotesi di una disfunzione del sistema degli oppioidi endogeni o degli endocannabinoidi non ha ancora guadagnato larghi consensi (Bowers et al, 2012;Preter et al, 2014). Il fumo di sigaretta è un riconosciuto fattore di rischio per l'insorgenza del DP (Moreno et al, 2014;Bakhshaie et al, 2016).…”
Section: Il Disturbo DI Panicounclassified
“…Growing evidence suggests that respiratory dysregulation is a central feature of PD. Klein and colleagues' 'suffocation false alarm' hypotheses regarding carbon dioxide hypersensitivity set the stage for the examination of the respiratory irregularities associated with panic disorder and related conditions 9,10 . In the case of panic disorder, chronic hyperventilation, lower end tidal CO 2 levels, respiratory rate and tidal volume irregularities, sighing, and breath-holding are characteristic features 11 .…”
mentioning
confidence: 99%